(untitled) (International Journal of Engineering and Computer Science, 2017)
The proposed system introduces a technology for the grasping of components, which is flexible and proposed for pick-andplace tasks with low manipulation complexity for industrial applications. Here it having two main characteristics: self adaptively and flexibility. Self-adaptively says that the proposed grasper can grip an object in a self-adaptive way such that various process complexities (e.g., sensing, force control, and sensor-motor coordination) are significantly reduced. In flexibility means by using a flexible material, a stable grip can be implemented.